Automation of building of behavior models of the non-markov discrete-continuous stochastic systems by the method of erlang phases - Volotchiy, Bohdan; Osirkovskyy, Leonid; Kulyk, Ihor (Видавництво Львівської політехніки, 2012)
The construction of models of behavior of discretecontinuous stochastic systems Non-Markov type by the method of Erlang phases is the object of consideration. This paper shows the principles of improving the technology of building the models of discrete-continuous stochastic systems, that allows you to build automated graph of states and transitions of Non-Markov type systems with using the method of Erlang phases. Improved technology is illustrated by the example of a queuing system.
Keywords: reliability; expanded Markov model; Non-Markov system; method of Erlang phases; queuing system